Decision making and framing effects in multiple sclerosis. (27th December 2020) - Zamarian, Laura; Berger, Thomas; Pertl, Marie‐Theres; Bsteh, Gabriel; Djamshidian, Atbin; Deisenhammer, Florian; Delazer, Margarete
Abstract: Background: Previous studies reported reduced decision‐making abilities for patients with multiple sclerosis (MS) relative to healthy controls (HC). This study aimed to evaluate whether these problems arise when sampling information or when pondering about the evidence collected. Methods: In a cross‐sectional, controlled study, 43 relapsing‐remitting MS patients (RRMS; Expanded Disability Status Scale 1.5, range 0–4) and 53 HC performed an information sampling task ('beads task'), a health‐related framing task, and neuropsychological background tests. Results: In the beads task, patients collected as much information as HC prior to a decision. However, there were twice as many patients as HC making irrational decisions, that is, decisions against the evidence collected (RRMS: 26/43, 60%; HC: 16/53, 30%; p  = 0.003). Compared to HC, patients also showed a stronger framing effect, that is, they were more strongly biased by the way health‐related information was presented ( p  < 0.05, Cohen's d  = 0.5). Overall, the framing effect predicted whether a participant would make irrational decisions (OR 2.12, 95% CI 1.29–3.49, p  < 0.001). Conclusions: Predecisional information sampling is intact in RRMS. However, compared to HC, patients are more likely to make irrational decisions and to be biased by the way health‐related information is framed. This warrants caution in communication, especially in the medical context, with patients. Abstract : This study shows that patients with multiple sclerosis (MS) collect as much information as healthy controls (HC) do prior to making a decision. However, twice as many patients as HC make irrational decisions, that is, decisions against the evidence collected. Compared to HC, patients also show stronger framing effects, that is, they are more strongly biased by the way health‐related information is presented. These results warrant caution in communication, especially in the medical context, with patients.